What is Needed to Improve Food Sales in Schools? Food Vendors’ Opinion from El Salvador - Hilari, Caroline; Franco, Margarita (Frontiers in Public Health, 2015)
Latin America and the Caribbean are at the forefront of the double burden of malnourishment, with rocketing rates of overweight, obesity and stagnant prevalence of stunting in many countries. School children are at a crucial age for setting eating habits, physical activity, nutritional status and long term outcomes both in their health as well as their education and economic productivity. Save the Children International implements a school health and nutrition program in 45 rural schools in El Salvador, Central America. The program aims at increasing the consumption of protein and micronutrients while reducing intake of sugar and fats in school children. In addition, there is great emphasis on food hygiene and safe handling, through training of the food vendors. We developed a conceptual framework for school nutrition programs that is phrased around five different moments: school snacks, school stores, nutrition learning, bringing food to school and eating at home. Monitoring and control lies in the hands of student brigades, which fosters child participation. We present findings of a qualitative evaluation on sale regulation in school food stores, documenting additional interventions that were needed to foster compliance. We explore how vendors are making money on healthy food if head teachers and parents are involved in regulating food stores and children are motivated to cherish fruits and vegetables. Based on these findings, we discuss a model of an enabling environment for healthy food at school.